PROSEDUR PEMERIKSAAN MASTOID DENGAN KASUS OTITIS MEDIA KRONIK (OMK) DI INSTALASI RADIOLOGI RSU ‘AISYIYAH PONOROGO - Amal Maaruf; Ike Ade Nur Liscyaningsih; Anshor Nugroho (JHN: Journal of Health and Nursing, 2026)
Chronic Otitis Media (COM) is an inflammation of the middle ear that can lead to intratemporal complications such as mastoiditis. Radiographic evaluation of the mastoid bone plays a crucial role in identifying structural damage and assessing the extent of infection. Theoretically, the Schüller method axiolateral projection involves a 45° head rotation and a 25°–30° caudal beam angulation. However, preliminary observations at the Radiology Department of 'Aisyiyah Ponorogo General Hospital revealed the use of a 40° caudal angulation. This study aimed to examine the mastoid examination procedure and the rationale behind the 40° caudal angulation at the Radiology Department of 'Aisyiyah Ponorogo General Hospital. A qualitative case study approach was employed at the facility between December 2025 and June 2026, involving interviews with three radiographers and one radiologist. Data collection was conducted through direct observation, interviews, and documentation. Data analysis was performed narratively—involving data reduction and presentation—followed by a comparison with theoretical standards and the drawing of conclusions. The results indicate that the mastoid examination is performed without special preparation, other than the removal of metal objects from the head area. Patients are positioned erect in a true lateral position, with the side of the head being examined placed against the detector. A bilateral Schüller method axiolateral projection is used, with a centering point 2–3 cm posterior-superior to the external auditory meatus (EAM), a 40° caudal beam angulation, and exposure factors of 70–80 kV, 200 mA, 16 mAs, and an FFD of 100–120 cm. The 40° angulation was selected to produce an elongation effect on the mastoid, thereby minimizing superimposition with surrounding bony structures, allowing for clearer visualization of mastoid air cells, and facilitating a comparison of the bilateral mastoid conditions. The study concludes that the mastoid examination procedure for patients with chronic otitis media (COM) at 'Aisyiyah Ponorogo General Hospital utilizes the bilateral axiolateral projection (Schüller method) with a 40° caudal angulation and no special preparation. This angulation aims to achieve optimal elongation of mastoid structures, minimize superimposition, and enhance the diagnostic accuracy for COM.